Expression of Ki-67, p53, α-SMA and COX-2 in lichen planus and related lesions: A pilot study - D.S. Sanketh; Karuna Kumari; Roopa S. Rao; Vanishree C. Haragannavar; Sachin C. Sarode; Gargi S. Sarode; A. Thirumal Raj; Shankargouda Patil (Elsevier, 2019)
Background: Researchers have struggled to understand the natural history of lesions presenting with both lichenoid features and epithelial dysplasia. Thus the present study was designed to differentiate between OLP, OLP with dysplasia, epithelial dysplasia and epithelial dysplasia with lichenoid features based on the expressions of ki-67, p53, COX-2, and α-SMA. Materials and methods: Formalin-fixed paraffin-embedded archival specimens of OLP, OLP with dysplasia, epithelial dysplasia and epithelial dysplasia with lichenoid features were subjected to immunohistochemical staining with ki-67, p53, COX-2, and α-SMA. Results: Ki-67 exhibited strong positivity in 100% (6/6) of epithelial dysplasia cases, 71.4% (5/7) of lichenoid dysplasia cases, 57.1% (4/7) of OLP cases and 60% (3/5) of OLP with dysplasia cases. Strong p53 staining was evident in more cases of lichenoid dysplasia [42.8% (3/7)], while moderate staining was more frequent in OLP cases [42.8% (3/7)] and OLP with dysplasia cases [42.8% (3/7)] and mild intensity was more frequent in epithelial dysplasia cases [50% (3/6)] followed by lichenoid dysplasia cases [42.8% (3/7)], OLP cases [28.5 (2/7)] and OLP with dysplasia cases [40% (2/5)]. COX-2 strong positivity was more frequent in cases of epithelial dysplasia cases [57.1% (4/7)] and OLP [50% (3/6)]. Strong α- SMA staining was noted more frequently in lichenoid dysplasia cases [71.4 (5/7)], followed by OLP cases [42.8% (3/7)] and OLP with dysplasia cases [60% (3/5)]. Conclusions: Ki-67, p53, α-SMA and COX-2 expression do not differentiate between OLP, LP with dysplasia and epithelial dysplasia with lichenoid features.